Performance Identification of Eutectic Fatty Acid-PLA Based Phase Change Material Board Installed in a Mini-Cubicle System - Aidy, Nurhanifa; Lindawati; Iqbal; Mahyuddin; Muhtadin; Muhammad Faisal; Yusrizal (LPPM Politeknik Aceh Selatan, 2026)
Thermal comfort regulation in buildings located in hot climates, such as Indonesia, remains highly dependent on air conditioning (AC) systems, leading to substantial energy consumption. Integrating Phase Change Materials (PCM) into building envelopes offers a passive thermal management strategy to reduce cooling loads. This study investigates the thermal performance of a gypsum-based wall incorporating a eutectic fatty acid PCM (laurate–stearate) of 85:15 (wt%) modified with polylactic acid (PLA) at three PCM:PLA ratios (1:0.6, 1:0.8, and 1:1), alongside a control sample without PCM. Samples were fabricated at laboratory scale and evaluated using a mini-cubicle system under controlled charging and discharging conditions. Energy performance was assessed through temperature change rates and heat transfer (q) analysis at three measurement points (T1, T2, T3). Results demonstrate that PLA modification significantly enhances PCM performance, with the 1:0.8 ratio (bPCM) exhibiting optimal behavior. During charging, bPCM achieved the lowest temperature change rates of 4.75 °C/h at T1, 1.15 °C/h at T2, and 0.65 °C/h at T3 and the minimum heat transfer from T2 to T3 of 32.049 J. Similarly, during discharging, bPCM maintained the smallest temperature change rates of 2.2 °C/h at T1, 1.0 °C/h at T2, and 0.65 °C/h at T3 with the lowest heat transfer to the indoor zone of 32.033 J. These findings confirm that optimized PLA-modified eutectic PCM significantly improves heat absorption, latent heat storage, and thermal insulation performance compared to non-PCM and non-optimized compositions. The proposed composite wall system demonstrates strong potential for passive cooling enhancement and building energy efficiency improvement in hot-climate regions